Brain Anomalies and Heart Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The type, frequency, and clinical presentation of developmental brain anomalies in 41 infants with the hypoplastic left heart syndrome are reviewed from the Children's Hospital of Philadelophia, and the University of Pennsylvania School of Medicine, Philadelphia.